Socio-demographic and Clinical Characteristics of patients with Thyroid Disorders in Erbil Governorate/Iraq - Al Barzanji, Bahjat Ahmad Mohamad; Mustafa, Ibrahim Hasan; Aziz, Kareem Fattah (Diyala Journal of Medicine, 2019)
Background: Thyroid disorder is one of the commonest disorder worldwide and also in Iraq. Objective: To study identify clinical presentations of thyroid disorder and its distribution in the terms of sex, age and residency. Classifying the patients who underwent operations according to types of the disease and complications were event after operations in Erbil Governorate. Patients and Methods: A retrospective study carried out in Hawler Teaching Hospital Out patients Clinic and privet clinic, from January 2014 to December 2018.Study involved 800 patients with goiter disordered who attended to hospital or private clinic. Data gathered by questionnaire which involved patients' socio-demographics data, signs and symptoms, clinical features of disorder, medical and surgical treatment offered to those patients, and the reports of complications' incidence that event in postoperative. Data were analyzed by the statistical package for the social science (SPSS, version 22) was used for data entry and analysis. Frequency and Percentages were used to identify distribution the disease, types, and complications. Results: There was high frequency of disorders among female 710 (88.7%) and adults, inconsistency of diseases' signs and symptoms among patients, highest percentage (44.2%) of patients were multinodular goiter, near to half of patients 392(49%) underwent operation and complications were reported with 42(10.7%) of patients after surgical operations. Conclusion: The proportion of female is high, there was high proportion of patients who needed to surgical treatment and there was proportion of patients with complications after surgical operations.